Interleukin (IL)-6 and IL-10 Are Up Regulated in Late Stage Trypanosoma brucei rhodesiense Sleeping Sickness - Kato, Charles D.; Alibu, Vincent P.; Nanteza, Ann; Mugasa, Claire M.; Matovu, Enock (PLoS Neglected Tropical Diseases, 2015)
Sleeping sickness due to Trypanosoma brucei rhodesiense has a wide spectrum of clinical presentations coupled with differences in disease progression and severity across East and Southern Africa. The disease progresses from an early (hemo-lymphatic) stage to the late (meningoencephalitic) stage characterized by presence of parasites in the central nervous system. We hypothesized that disease progression and severity of the neurological response is modulated by cytokines.
Keywords: Interleukin; Sleeping Sickness; Trypanosoma brucei rhodesiense